Pharmacological importance of Peach Gum Polysaccharide: a review - Goh, Ken Yong *; Gew, Lai Ti * (Bentham Science, 2022)
Background: Peach gum is a natural gum exudate secreted from a peach tree (Prunus persica) by a process known as physiological gummosis. Peach gum is a natural biopolymer that is composed of acidic polysaccharides with a high percentage of arabinose and galactose subunit, which classifies it as an arabinogalactan.